Designing and Implementing Information Display Consoles for Lecturers - Muhammad Arif, Ahmad Rizal (Universiti Teknologi Petronas, 2004)
This report is about an Information Display Console (IDC) project that is to be used by each lecturer in Universiti Teknologi PETRONAS (UTP). The purpose of this IDC is to give information to students or lecturers while the particular lecturer is away and to enhance the professionalism in communication among lecturers and students. The system consists of two parts. Firstly is the transmitter which is connected to a computer via parallel port. Second part is the receiver to which a Liquid Crystal Display (LCD) is attached. The system uses the infrared communication in transmitting data that need to be updated. The data will be stored in a memory and will be displayed continuously. The users can use a computer with its user interface to update the new data. The development of the project involves designing and implementing the hardware and the software. In the hardware part, it discusses the circuit design including the calculation. In the software part, it discusses the process of developing the graphical user interface (GUI), which is to be used in the system. The discussion on testing and debugging the system are also included. The system is a pioneer system in UTP since it uses new design in hardware and software development. With this successful prototype development, it is envisioned that lectures can enhance their professionalism in communication. Perhaps the system could be deployed in UTP widely.